Técnicas de amostragem utilizadas pelos serviços de auditoria interna de empresas no Brasil: um estudo de casos - Oliveira, Francisco Neves (1989)
The objective of this paper was to explore the existing relationship between the literature about auditing sampling techniques and the techniques effectively utilized by the internaI auditing services in the companies in Brazil. It sought to analyze which were the main problems found in the utilization of these techniques, and yet verify if there were differences with respect to the use of more sophisticated sampling techniques utilized by national private companies governmentals and companies of external origino (Chapter I) The revision of literature, had the objetive to disclose and summarize a few of the many sampling techniques which the internal auditing of the frrms have at their disposal. (Chapter lI) Following, the methodology utilized in the research and the respective reason for its use were disclosed. (Chapter 1I1) The description of the cases, realized through the questionaire in the nine frrms, appeared in this chapter, where each case was described individually. (Chapter IV) The results obtained were analyzed in accordance with each item of the questionaire making it possible an over alI analyzis of the sampling techniques utilized by the internal auditing services of the frrms in Brazil. (Chapter V) Finally, after presenting the summary and the conclusions of the research at the light of the theorical basis, recommendations and suggestions were formulated for future researches. (Chapter VI)